Man and his thermal environment - Clark, R. P; Edholm, O. G. 1909-1985 (Arnold, 1985)
Topics covered include: The thermal environment, Environmental and physiological measuring techniques, Skin temperature, Convection, Heat transfer by radiation, evaporation and conduction, Temperature and the circulation, Man is a tropical animal, Responses to cold, Perception and appreciation of the thermal environment, Clothing and The built environment.